(3GdMeGjI GdLfGFjI ddHWGbGJ GdeUQajI GdeeZfWI (B/ s - (3MeO MejO LeYg GdeQGTOg s; (3YeQ eMeO eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3eY MOGKI ONhd GdHWGbGJ GdeUQajI GdeeZfWI ddShb GdYQHjI(B: (3hYOe EdeGe GdcKjQ ef MGedgG hGdJLGQ HcjajI GQJcGH LQGFe GdHWGbGJ GdeUQajI GdeeZfWI(B: (3hGdCSGdjH GdGMJjGdjI ef bHd eMJQaj gPg GdfhYjI ef GdLQGFe(B: (3aEffG fchf aj MGLI eGSI Edi MeGjI LfGFjI NGUI(B: (3ojSJWGY ef NdGdgG aQV GdYbhHGJ Ydi cd aYd jQbi Edi GdEVQGQ HGdBNQjf(B: (3hgOa GdHMK Edi JYQja GdHWGbGJ GdeUQajI GdeeZfWI(B: (3hCfhGYgG(B: (3hcjajI GdJejjR HjfgG(B: (3hJhUja GdWHjYI GdbGfhfjI ddHWGbGJ GdeUQajI GdeeZfWI(B: (3hcPdc TQM GdMeGjI GdLfGFjI GdYGeI hGdNGUI ddHWGbGJ GdeUQajI GdeeZfWI(B. (3hJe JfGhd gPG GdHMK aj aUdjf jSHbgeG aUd JegjOj (B. (3hJhUd GdHGMK Edi YOO ef GdJhUjGJ efgG (B: (3hVY VhGHW dYedjGJ EUOGQ hGSJNOGe HWGbGJ GdGFJeGf GdGdcJQhfjI eY VQhQI JbjO GdeUGQa HgPg GdVhGHW(B: (3hCjkVG JfXje OhQGJ JOQjHjI dQLGd GdCYeGd GdYQH hCUMGH GdeJGLQ hGdeMdGJs
With the recent entry of magnetic bank cards for the Arab market, and lack of familiarity with many of the holder and traders how to commit magnetic bank cards crimes, fraudulent and methods by this quality professionals of the crimes, then we are in dire need of a special criminal protection, canned from which to impose sanctions on any act tantamount to harm others, and the goal of research is to identify the magnetic bank cards, types, and how to distinguish them, and characterization of the legal nature of banking cards, magnetic, as well as explain the public and private criminal protection for banking cards magnetized. This research was addressed in two chapters preceded by an introductory chapter. The researcher found a number of recommendations, including: controls for issuing operations and the use of electronic credit cards with banks need to comply with these regulations, and also organize training courses for Arab businessmen and shopkeepers and shops mode.
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B114-124s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdHWGbI GdGFJeGfjI s; (3GdHWGbI GdeUQajI s; (3GdMeGjI GdLfGFjI s; (3HWGbI VeGf GdTjcGJs; (3ehXa GdHfcs; (3GdGSJjdGAs; (3GdHWGbI GdedZGIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs